EVALUATION OF THE RHEOLOGICAL CHARACTERISTICS OF GEAR OILS UNDER UNSTEADY FRICTION CONDITIONS - Mikosianchyk, Oksana; Ilina, Olha (Problems of Friction and Wear, 2024)
The aim of the study was to evaluate the rheological characteristics of the lubricant during the formation of hydrodynamic and nonhydrodynamic components of the lubricating layer in tribotechnical contact. Two gear oils for hypoid gears were chosen as lubricants for the study. The studies were carried out on a hardware and software complex using a roller analogy that modeled the operation of gears under rolling and slipping conditions. The ‘Bora B’ T-Shyp gear oil (sample 1) is characterized by more effective rheological characteristics under unsteady friction conditions in the rolling sliding mode (30%), compared to the T-Shyp gear oil for hypoid gears (sample 2) due to the greater resistance of the boundary layers to the deformation rate of the lubricant under conditions of increasing the shear rate gradient. The non-Newtonian properties of oils according to the Ostwald-de Weyl power law are considered and the manifestation of pseudoplastic properties by lubricants is substantiated - the model of the behavior of gear oils corresponds to pseudoplastic fluids with a degree index n of 0.45...0.85. The expediency of using the Barus dependence to estimate the viscosity of a lubricant at a contact pressure of 200 MPa is analyzed. It is substantiated that when using the Barus dependence to calculate the viscosity of a lubricant, it is necessary to take into account the change in the piezoelectric viscosity coefficient, taking into account the manifestation of non-Newtonian properties in the formation of boundary layers of the lubricant. The regularities of changes in the elastic and viscous components of stress in the lubricant under conditions of increasing the gradient of the shear rate at friction are established. With an increase in the shear rate gradient from 2.5∙102 to 7.4∙105 s-1, the deformation rate increases by a factor of 2.9∙103, and the destruction of boundary layers occurs. At the same time, the lubricant loses its pseudoplastic properties and becomes a Newtonian fluid, the elastic component of the stresses under such conditions being zero.